INTERRELATIONS OF SERVICE BEHAVIOUR AND SEMINAL ATTRIBUTES OF HAMPSHIRE BOARS - CHUTIA, T; TAMULI, MK; BISWAS, RK; DEKA, BC; SINHA, S; GOSWAMI, J (The Indian Journal of Animal Reproduction, 2022)
Forty ejaculates form five Hampshire boars (8 from each) were collected by simple fist method using a dummy. The service behaviour in terms of reaction time was positively correlated (p
Keywords: Breeding soundness; Hampshire boar; Semen; Seminal characters; Service behaviour